O estudo dos vertebrados como um aspecto da educação ambiental - Moura, João Paulo da Silva (2019)
Faced with the growing need to work scientifically on knowledge, which is present in the lives of each of us, especially with the students of the public schools of Brazil, the teaching of Biology has the role to stop being merely a transmission of knowledge and lead the construction of intellect and creative thinking, as well as all the science that seeks to develop knowledge for life. In this sense, the teaching of Zoology goes through several problems. The present research had as problematization the following question: How to work in a pertinent way the contents of Zoology, specifically the Zoology of Vertebrates in High School, using strategies and alternative teaching resources, based on the local experience and reality of the students and based on the principles of Environmental Education, to try to ensure meaningful learning? Therefore, the objective was to investigate the relationship of the teaching of Vertebrate Zoology and Environmental Education in High School and strategies that aim at the best learning within the discipline of Biology. The subjects were students of the second year of high school, aged between 14 and 17 years, from a public school in the city of Paulo Afonso, in the interior of Bahia, and ten professors of Biology of public schools of the same city. Scientific research has made use of strategies and alternative teaching resources based on the construction of Didactic Sequences on Vertebrate Zoology (the result of this research) of students 'and teachers' experience, knowledge of local fauna and knowledge about Environmental Education, a descriptive research of qualitative character, with data collection through the application of questionnaires and content analysis. The research was applied in two classes, where one group experienced the alternative teaching strategies elaborated (with use of the product) and another group participated only in expositive classes based on traditional teaching, and with this one can compare results in the construction of knowledge within the theme in question. The product, the Didactic Sequences based on strategies and diversified resources, about teaching Vertebrate Zoology was compiled in the form of textual material that can be adapted to the classroom. Finally, it was found that alternative teaching strategies favored the construction of students' scientific knowledge, in contrast to the lectures and traditional teaching, giving them autonomy, valuing the work of the biology teacher and developing essential skills of the scientific methodology related to knowledge of Zoology and Environmental Education.